Cytotoxic Activity of Melaleuca sp. and Eucalyptus sp. Essential Oils Against Breast Cancer MCF-7 Cells and Their Potential Role in Chemotherapy - Sukma Diani Putri; Ike Puspitaningrum; Sally Yustinawati Suryatna (Poltekkes Kemenkes Semarang, 2026)
Breast cancer remained one of the leading causes of cancer-related deaths among women, motivating the search for effective and accessible therapeutic support. Essential oils from Melaleuca sp. and Eucalyptus sp. had been reported to contain bioactive compounds with anticancer potential. This study aimed to compare their antiproliferative effects when combined with doxorubicin on MCF-7 breast cancer cells in vitro. MCF-7 cells were seeded in 96-well plates and treated with increasing concentrations of each essential oil together with doxorubicin for 48 hours. Cell viability was assessed using the resazurin assay. Both treatments reduced cell viability in a concentration-dependent manner. The combination of Melaleuca sp. and doxorubicin showed stronger inhibition, with an IC₅₀ of 0.1576 µg/mL, while Eucalyptus sp. and doxorubicin produced an IC₅₀ of 0.7792 µg/mL. These findings suggested that Melaleuca sp. demonstrated higher potency under the tested conditions. However, the absence of a doxorubicin-only control limited the interpretation of whether the effects were synergistic or simply additive. In conclusion, Melaleuca sp. appeared to have greater potential as a supportive natural agent in breast cancer treatment. Further studies were recommended to include full drug controls and mechanistic assays to better clarify the interaction with chemotherapy.